Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.25259/sni-82-2019
|View full text |Cite
|
Sign up to set email alerts
|

Conditions associated with giant pituitary tumors at the time of surgery effecting outcome morbidity and mortality

Abstract: Background: Surgical outcome prediction has assisted physicians in discussing surgical intervention or expectant management. While increasing pituitary tumor size would seem to be associated with increasing challenge of removal and associated complications, that relationship has not been borne in the literature. Methods: We performed a retrospective review of a consecutive cohort of pituitary surgeries completed at our institution. Data included age at the time of surgery, presenting symptoms and Glasgow Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our study identified several preoperative MRI predictive factors of complications, including larger main diameter, cerebral artery encasement, suprasellar extension with a “narrow neck” aspect, or hydrocephalus. Some of these predictive factors have been reported by most prior studies ( 9 , 11 , 52 ). In clinical practice, the observation of pejorative preoperative features should lead to patients being informed about the increased risk of complications.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our study identified several preoperative MRI predictive factors of complications, including larger main diameter, cerebral artery encasement, suprasellar extension with a “narrow neck” aspect, or hydrocephalus. Some of these predictive factors have been reported by most prior studies ( 9 , 11 , 52 ). In clinical practice, the observation of pejorative preoperative features should lead to patients being informed about the increased risk of complications.…”
Section: Discussionmentioning
confidence: 60%
“…Giant adenomas are usually revealed by visual deterioration, endocrine dysfunction or cognitive disorders ( 9 ). Except for giant prolactinomas and rare giant somatotroph adenomas with a significant response to somatostatin analogues, surgery is usually indicated, with the main objective of visual pathways decompression and maximum volume reduction ( 8 , 10 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although the size may be a key factor in injuring the AOP, these complications have rarely been reported. [24][25][26][27][28][29] Only Yano et al reported on a series of giant adenomas where there were two perforator injuries in two tumors (one with superior and the other with posterior extension). 21 The most common complications in these large and giant tumors usually tend to be diabetes insipidus, 21,24,25,27,28,[30][31][32][33] postoperative cerebrospinal fluid leak, 21,27,28,30,[32][33][34] and new pituitary insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases noted above, the cerebral ischemia was the cause for the patient's presentation to the hospital; it is noteworthy to address that the patient in our report did not have her stroke until after surgery. There are only 11 reported cases of ischemic infarction occurring after surgical removal of a pituitary mass, 10 of which occurred in the setting of vasospasm and 1 in the setting of thrombosis [15][16][17][18]. Vasospasm is a rarely documented complication after pituitary surgery, with 30 cases reported in the literature [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note however that either of these can be done to definitively determine the cause of the ischemia; this is significant as treatment options vary based on the underlying cause. In one very small retrospective study done in patients with pituitary adenoma removal, all patients with a postoperative decline in Glasgow Coma Scale (GCS) were found to have either ischemic infarct or hemorrhage, both associated with vasospasm [17]. This highlights the importance of considering these as possibilities in patients with a postoperative decline in decline in mental status and obtaining the appropriate imaging in a timely manner to allow for intervention.…”
Section: Discussionmentioning
confidence: 99%